Protecting the authenticity and integrity of inuksuit within the arctic milieu - Heyes, Scott (Études/Inuit/Studies, 2002)
AbstractThis paper explores the legacy of the stone cairn beacons known as inuksuit — intriguing stone formations built by the Inuit for the last 4000 years that describe messages about landscape, convey messages about way-finding and communicate stories about place. Although inuksuit appear as ancient artefacts of a by-gone era, they have survived well into the twenty-first century, withstanding the changes that have dramatically impacted other traditional facets of Inuit life. Inuksuit remain as solidified fingerprints on the landscape, marking ancient and modern navigation routes. They are signs in themselves and signs that converge to form maps. The power and legacy inuksuit exert over the landscape is, however, potentially at risk from mining and hydro-electricity developments that are planned to consume further areas of the Arctic. Moreover, particular marketed forms of inuksuit threaten to taint and avert the original inuksuit function. A case for preserving inuksuit is indeed strong, and perhaps quite necessary considering they are one of the few remaining tangible fabrics of Inuit society that continue to function within an original setting.